Friday

March 6, 2015

March 6, 2015

Posted by **ridhi** on Friday, May 4, 2012 at 7:30am.

- maths -
**Steve**, Friday, May 4, 2012 at 12:11pma+(p-1)d = q

a+(q-1)d = p

(p-1)d-q = (q-1)d-p

[(p-1)-(q-1)]d = q-p

(p-q)d = q-p

d = (q-p)/(p-q) = -1

Tn = Tq + (n-q)d

= p + (n-q)(-1)

= p+q-n

- maths -
**ridhi**, Saturday, May 5, 2012 at 2:53amthnaks :)

**Answer this Question**

**Related Questions**

Math - The nth term of an A.P. Is 3 times the 5th term.(a)find the relationship ...

maths - In an AP the first term is 2 and the nth term is 29 and the sum of the n...

Precalc - Find a formula for the nth term if... a)the 8th term is 8 and the 20th...

Maths - The 3rd term of an AP is 10 more than the first term while the fifth ...

maths - Given that the first term of an A.P is 7 and its 10th term is twice its ...

maths - if the seventh term of an AP is zero,prove that its 27th term is five ...

Maths - If 9th term of an arithmetic progression is 0, prove that its 29th term ...

Maths - The 5th term of an exponential sequence is 4 and of 2nd term is 35(¡)...

Math - 3,5,-5... The first term in the sequence of #'s shown above is 3. Each ...

Sequence - Find the common difference and a formula formula for the nth term of ...